Metabolite Support of Long-Term Storage of Sperm in the Spermatheca of Honeybee (Apis mellifera) Queens - Liu, Zhenguo; Liu, Feng; Li, Guilin; Chi, Xuepeng; Wang, Ying; Wang, Hongfang; Ma, Lanting; Han, Kai; Zhao, Guangdong; Guo, Xingqi; Xu, Baohua (Frontiers in Physiology, 2020)
The polyandrous mating system of honeybees (Apis mellifera L.) has garnered widespread attention. Long-lived honeybee queens only mate early in maturation, and the sperm obtained from the aerial mating is stored in the spermatheca. The maintenance of sperm viability in the spermatheca is an intriguing and complex process. However, the key physiological and biochemical adaptations underlying the long-term storage of sperm remain unclear. Analysis of the metabolite profile could help better understand the biology of the spermatheca and offer insights into the breeding and conservation of honeybees and even pest control strategies. Here, the changes in metabolites in the spermatheca were quantified between virgin queens and new-laying queens (with stored sperm) via liquid chromatography–mass spectrometry. Compared with virgin queens, changes occurred in lipids and lipid-like molecules, including fatty acyls and glycerophospholipids (GPL), prenol lipids, and sterol lipids, during storage of sperm in new-laying honeybee queens. Furthermore, the metabolic pathways that were enriched with the differentially expressed metabolites were identified and included GPL metabolism, biosynthesis of amino acids, and the mTOR signaling pathway. The likely roles of the pathways in the maintenance and protection of sperm are discussed. The study identifies key metabolites and pathways in the complex interplay of substances that contribute to the long-term storage of sperm and ultimately reproductive success of honeybee queens.